The right of defence: is it a guarantee that is really respected? - Torres Morales de Ferreyros, Sylvia Amelia (2008)
The present work intents to highlight the problematic that appears when it is tried to exert one of the fundamental rights that is clearly recognized in our Constitution: the right of defense. Nowadays we can not deny that despite of the fact that we count on clear concepts on the right: «We all have the right to a defense» and «We all are innocent until proven guilty» (innocence presumption), we are very far from guaranteeing in a legitimate way that all this is fulfilled. The work will explore the regulation of this rights and the problems that we found that contaminates and appear like constant obstacles so that this one can suitably be exerted.